SCREENING OF EXTRACELLULAR LIPASE RELEASING MICROORGANISMS ISOLATED FROM SUNFLOWER VEGETABLE OIL CONTAMINATED SOIL FOR BIO-DIESEL PRODUCTION - NARASIMHAN V; VALENTIN BHIMBA B (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Â Objective: Biological conversions of renewable vegetable oil into bio-diesel are going to become one of the future energy resources for the world. Methods: Soil samples spilled with sunflower oil decomposes, collected from a sunflower oil refinery is used for screening fungal strains. Potato dextrose agar plates were used to isolate, purify the fungal species. Lipase activity of the extracellular lipase enzyme producing fungal species was tested with tween 80, rhodamine-B and phenol red containing agar plates. Results: Five differently colored fungal strains were observed, isolated, purified and compared for their lipolytic activity. Conclusion: A brown colored fungal colony was observed to have the highest lipase activity towards the log chain glycerides. Keywords: Lipase enzyme, Aspergillus fungal species, Characterization.